2012
DOI: 10.9744/jmk.13.2.135-150
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kondisi Pemangku Kepentingan Dalam Keberhasilan Proyek

Abstract: ABSTRAKAda suatu kecenderungan yang alamiah dari kelompok pemangku kepentingan untuk mencoba mempengaruhi kondisinya dalam keberhasilan proyek. Gambaran ini merupakan tantangan bagi pelaku jasa konstruksi untuk menganalisis dan mangelola berbagai perhatian dan kebutuhan dalam pelaksanaan proyek konstruksi. Tujuan dari penelitian ini adalah untuk mengetahui seberapa baik faktor-faktor yang mempengaruhi kondisi pemangku kepentingan dalam keberhasilan proyek. Faktor kondisi ketidakpastian yang datang dari pemangk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
(61 reference statements)
1
2
0
4
Order By: Relevance
“…Based on the results of hypothesis testing on the research model, it can be seen that in the H1 hypothesis there is a significant relationship between domination and project performance can be proven. This hypothesis finds the same results as research conducted by Sanggoro (2020) and Chandra (2011) which concluded that there was a significant influence of stakeholder domination on project performance. In general, with this measurement model, the influence of Domination is still quite strong in its role in building projects.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Based on the results of hypothesis testing on the research model, it can be seen that in the H1 hypothesis there is a significant relationship between domination and project performance can be proven. This hypothesis finds the same results as research conducted by Sanggoro (2020) and Chandra (2011) which concluded that there was a significant influence of stakeholder domination on project performance. In general, with this measurement model, the influence of Domination is still quite strong in its role in building projects.…”
Section: Discussionsupporting
confidence: 84%
“…With such a large portion, the achievement of project cost and time definitely rises the expectation of all stakeholders. There are many projects that fail, one of which is because the project manager cannot manage the stakeholders, whereas project performance is highly dependent on the attention to the stakeholders (Chandra et al, 2011). In the 2018 project on the Design and Build of the School Building Total Rehabilitation in the Special Capital Region of Jakarta Province, there were a total of 98 school buildings which were divided into five projects.…”
Section: Introductionmentioning
confidence: 99%
“…Posisi pemangku kepentingan dalam mencapai keberhasilan proyek itu ternyata penting [2]. Dimana proyek adalah upaya sementara untuk membuat produk, layanan, atau keluhan unik melalui keterlibatan berbagai pemangku kepentingan, desain, persyaratan, kontraktor, pemilik, atau pemangku kepentingan di situs.…”
Section: Pendahuluanunclassified
“…Pemangku kepentingan atau disebut juga dengan stakeholder merupakan pihak yang dapat mempengaruhi maupun menerima dampak dari keputusan yang diambil (Freeman, 1984). Arti lain mengenai stakeholder yaitu sebagai masyarakat, baik individual maupun kelompok, yang memiliki legitimasi, kekuasaan, dan kepentingan terhadap keberhasilan perusahaan (Chandra, Indarto, Wiguna, & Kaming, 2011 Ma, Wang, Wu, & Tseng, 2018). Adanya komunitas di lingkungan perusahaan juga perlu dipertimbangkan sebagai stakeholder yang penting dikarenakan komunitas dapat mempengaruhi fleksibilitas dari keberlanjutan perusahaan, baik dari sisi lingkungan, ekonomi, dan sosial (Bridger & Luloff, 1999;Henson, 2016;Roseland, 2000;dalam Ma, Wang, Wu, & Tseng, 2018).…”
Section: Tinjauan Pustakaunclassified